Preparation method of ion exchange membrane with permeation surface orientation structure

By performing ion replacement before film preparation and using a mixed solvent with a boiling point difference of no more than 4 degrees Celsius under normal pressure conditions, combined with magnetic field conditions, the problem of low degree of permeability of the existing ion exchange membrane is solved, and more efficient ion transport performance is achieved.

CN119798746AActive Publication Date: 2025-04-11TIANJIN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510308294.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-04-11
Estimated Expiration
2045-03-17

AI Technical Summary

Technical Problem

The degree of transmission surface orientation of the existing ion exchange membrane is low, resulting in poor ion transport performance and affecting the efficiency of the electrochemical energy conversion device.

Method used

The method of mixing a mixed solvent with a boiling point difference of no more than 4 degrees Celsius under normal pressure conditions is used to prepare an ion exchange membrane under magnetic field conditions to improve the degree of its permeability orientation structure.

Benefits of technology

The orientation degree of the ion exchange membrane and the ion transport performance in the transmission plane direction are significantly improved, and the efficiency of the electrochemical energy conversion device is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a preparation method of an ion exchange membrane with a permeation surface orientation structure, which comprises the following steps: carrying out ion replacement on a plurality of polymers and fillers which all or partially contain magnetic responsive structures before preparing a membrane by using an ion displacer aqueous solution, washing off redundant ions, and dissolving in a single solvent to prepare a membrane preparation solution; or ion replacement before film preparation is not carried out, and a mixed solvent with the boiling point difference not greater than 4 DEG C under the normal pressure condition is dissolved to prepare a film preparation solution, or a treatment technology combining the two is adopted; pouring the membrane preparation liquid into a culture dish, and evaporating the solvent to form a membrane at a certain vertical magnetic field intensity and a certain temperature; and carrying out alkalization or acidification treatment to obtain the ion exchange membrane with the permeation surface orientation structure. Under the conditions of the same membrane preparation raw materials and the same magnetic field intensity, the magnetic response capability of the membrane preparation liquid can be enhanced, the aggregation size and the orientation regularity of the hydrophilic phase in the whole membrane preparation process are improved, and the remarkable ion transmission performance benefit in the membrane permeation surface direction is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of new materials, and in particular to a method for preparing an ion exchange membrane with a permeable surface orientation structure. Background Art

[0002] Ion exchange membranes are key materials in clean energy or new energy storage fields such as fuel cells, water electrolyzers, ion batteries, and flow batteries. In the actual electrochemical energy conversion devices in these application fields, the ion exchange membrane is located between the electrodes on both sides, and ions need to pass through the permeable surface direction of the ion exchange membrane (that is, the through-surface direction, the thickness direction) to transport across the membrane to achieve energy conversion. However, ion exchange membranes prepared by general membrane preparation methods usually have an isotropic ion transport structure, which is not conducive to the rapid transmembrane transport of ions between the two electrodes along the shortest path along the permeable surface direction of the membrane.

[0003] In order to improve the energy conversion efficiency, the ideal ion exchange membrane should have a permeate-oriented transport structure. Although there are some reports on the use of electric and magnetic fields to construct a permeate-oriented transport structure in the ion exchange membrane, the degree of orientation is low and the advantage of ion conductivity concentrated in the permeate direction is not obvious.

[0004] In the related technology, for example, Chinese patent publication number CN109078501A discloses a method for preparing an ion exchange membrane with an ordered ion conduction structure. This patent can orderly regulate the ion conduction structure of the ion exchange membrane to prepare an efficient and durable ion exchange membrane with an ordered ion conduction structure.

[0005] However, existing reports are limited to the synthesis of polymers or fillers with electric or magnetic field responsiveness and the formation of films under electric or magnetic field conditions, but lack comprehensive consideration and optimization of the entire film-forming system and process, such as the influence of ions and solvents in the film-forming solution.

[0006] Therefore, this research field urgently needs to develop a more holistic membrane preparation method to improve the orientation degree of ion exchange membranes, so as to obtain more significant ion transmission performance benefits in the direction of the permeable surface, thereby further improving the efficiency of related electrochemical energy conversion devices. Summary of the invention

[0007] In order to solve the above problem, the present invention provides a method for preparing an ion exchange membrane with a permeable surface orientation structure to solve the problem.

[0008] In order to achieve the above objectives, this application provides the following technical solutions:

[0009] A method for preparing an ion exchange membrane having a permeable surface oriented structure comprises the following steps:

[0010] S001: Using polymer A having a magnetically responsive structure alone or using one of the following compositions, ion replacement is performed before film formation in an ion replacement agent aqueous solution, and then the excess ions are washed away and dissolved in a single solvent to prepare a film-forming solution;

[0011] The composition comprises: composition ① and / or composition ②:

[0012] The composition ① is a combination of any two of the polymer B, the polymer A having a magnetic responsive structure, and the filler a having a magnetic responsive structure;

[0013] The composition ② is a combination of polymer B, polymer A having a magnetic responsive structure and filler a having a magnetic responsive structure;

[0014] S002: pour the film-making solution into a culture dish, and evaporate the solvent for 12-48 hours to form a film under the conditions of a vertical magnetic field strength of 0.001-5 Tesla and a temperature of 40-120°C;

[0015] S003: The formed membrane is subjected to alkalization or acidification treatment to obtain an ion exchange membrane having a permeable surface oriented structure.

[0016] It is further configured that: in step S001, the membrane-making solution can also be made by the following steps:

[0017] A polymer A having a magnetically responsive structure is used alone or one of the following compositions is used, dissolved in a mixed solvent having a boiling point difference of no more than 4 degrees Celsius under normal pressure to prepare a membrane-forming solution;

[0018] The composition comprises:

[0019] ①: A combination of any two of polymer B, polymer A having a magnetically responsive structure, and filler a having a magnetically responsive structure;

[0020] ②: A combination of polymer B, polymer A having a magnetically responsive structure, and filler a having a magnetically responsive structure.

[0021] It is further configured that: in step S001, the membrane-making solution can also be made by the following steps:

[0022] The polymer A having a magnetically responsive structure is used alone or one of the following compositions is used to perform ion replacement in an ion replacement agent aqueous solution before film formation, and after washing away excess ions, the solution is dissolved in a mixed solvent having a boiling point difference of no more than 4 degrees Celsius under normal pressure to prepare a film-forming solution;

[0023] The composition comprises:

[0024] ①: A combination of any two of polymer B, polymer A having a magnetically responsive structure, and filler a having a magnetically responsive structure;

[0025] ②: A combination of polymer B, polymer A having a magnetically responsive structure, and filler a having a magnetically responsive structure.

[0026] It is further configured that the polymer main chain in the polymer A is one of polyimide, polyamide, polyetheretherketone, polysulfone, polyethersulfone, polytetrafluoroethylene, polydimethylsiloxane, polystyrene, polybenzimidazole, polyphenylene oxide, polyethylene, polyvinyl chloride, polyvinyl pyridine or polyvinyl cyclohexane.

[0027] It is further configured as follows: the magnetic responsive structure of the polymer A is one of a ferrocenium cation group, a cobaltocene cation group, a nickelocene cation group, and a ferrocyanide coordination group.

[0028] It is further configured as follows: the filler a is one of modified iron oxide particles, modified erbium oxide particles, modified carbon nanotubes, modified halloysite, modified rectorite, modified montmorillonite, modified silica, modified titanium dioxide, modified graphene, modified graphene oxide, modified boron nitride or modified nitrogen carbonide.

[0029] It is further configured that: the magnetic responsive structure of the filler a is iron oxide, erbium oxide or a Prussian blue analogue.

[0030] It is further configured that: the polymer B is one of polyimide, polysulfone, polyethersulfone, polystyrene, polyphenylene sulfide, polyvinylpyridine, polypropylene, polyacrylonitrile, polyphosphazene, polyvinylidene fluoride or polymethyl methacrylate.

[0031] It is further configured as follows: when the polymer A and polymer B are used to prepare the membrane-forming liquid, the mass ratio is (1-99): (1-99); when the polymer A and filler a are used to prepare the membrane-forming liquid, the mass ratio is (50-99): (1-50); when the polymer B and filler a are used to prepare the membrane-forming liquid, the mass ratio is (50-99): (1-50); when the polymer A, polymer B and filler a are used to prepare the membrane-forming liquid, the mass ratio is (1-98): (1-98): (1-50).

[0032] It is further configured that the ion replacement agent is one of sodium molybdate, sodium tungstate, potassium tetrafluoroborate, potassium hexafluorophosphate, potassium hexafluoroantimonate, lithium bis(trifluoromethanesulfonyl imide), gadolinium nitrate, terbium chloride, dysprosium chloride, holmium nitrate, erbium nitrate, and thulium bromide.

[0033] It is further configured as follows: the single solvent is one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, and m-cresol.

[0034] It is further configured as follows: the mixed solvent having a boiling point difference of no more than 4 degrees Celsius under normal pressure conditions is a group selected from N,N-dimethylformamide and 1-methylcyclohexanol, N,N-dimethylacetamide and 2-methylcyclohexanol, dimethyl sulfoxide and 3-nonanol, dimethyl sulfoxide and 1,2-butanediol, dimethyl sulfoxide and 2-ethylbutyric acid, N-methylpyrrolidone and 5-methyl-5-nonanol, N-methylpyrrolidone and α-phenylethanol, m-cresol and 5-methyl-5-nonanol, and m-cresol and α-phenylethanol.

[0035] It is further set as follows: the volume ratio of the two solvent components in the mixed solvent with a boiling point difference of no more than 4 degrees Celsius under normal pressure conditions is (10~90): (10~90).

[0036] It is further configured as follows: the modification is surface quaternization, or a three-step combination of surface Prussian blue analog coating electrodeposition-catechol coating deposition-sulfonation.

[0037] Compared with the prior art, the beneficial technical effects of the present invention are:

[0038] The present invention adopts the treatment technology of ion replacement before film making, mixed solvent with boiling point difference of no more than 4 degrees Celsius under normal pressure to prepare film making liquid, or the combination of the two. Under the condition of the same film making raw materials and the same magnetic field strength, the magnetic response ability of the film making liquid can be enhanced, and the aggregation size and orientation regularity of the hydrophilic phase in the whole film making process can be improved. This method breaks through the limitation of only synthesizing polymers or fillers with electric field or magnetic field responsiveness and making films under electric field or magnetic field conditions, and comprehensively considers and optimizes important factors such as ions and solvents in the whole film making system and process, greatly improves the orientation degree of ion exchange membrane, and obtains more significant ion transmission performance benefits in the direction of the through surface. DETAILED DESCRIPTION

[0039] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present application. It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be arbitrarily combined with each other.

[0041] In some exemplary embodiments, the present invention discloses a method for preparing an ion exchange membrane having a permeable surface oriented structure, comprising:

[0042] Separately polymer A;

[0043] and / or combining any two of the polymer B, the polymer A having a magnetic responsive structure, and the filler a having a magnetic responsive structure;

[0044] and / or combining polymer B, polymer A having a magnetically responsive structure and filler a having a magnetically responsive structure, performing ion replacement in an ion replacement agent aqueous solution before film formation, washing away excess ions and then dissolving in a single solvent to prepare a film-forming solution;

[0045] Furthermore, the film-making solution can also be prepared by the following steps:

[0046] Separately polymer A;

[0047] and / or combining any two of the polymer B, the polymer A having a magnetic responsive structure, and the filler a having a magnetic responsive structure;

[0048] and / or the polymer B, the polymer A having a magnetic responsive structure and the filler a having a magnetic responsive structure are combined and dissolved in a mixed solvent having a boiling point difference of no more than 4 degrees Celsius under normal pressure to prepare a membrane-forming solution;

[0049] Furthermore, the membrane-making solution can also be prepared by the following steps:

[0050] Separately polymer A;

[0051] and / or combining any two of the polymer B, the polymer A having a magnetic responsive structure, and the filler a having a magnetic responsive structure;

[0052] and / or combining polymer B, polymer A having a magnetically responsive structure and filler a having a magnetically responsive structure, performing ion replacement in an ion replacement agent aqueous solution before film formation, washing away excess ions and then dissolving in a mixed solvent having a boiling point difference of no more than 4 degrees Celsius under normal pressure to prepare a film-forming solution;

[0053] Pour the film-making solution into a culture dish, and evaporate the solvent for 12-48 hours to form a film under the conditions of a vertical magnetic field strength of 0.001-5 Tesla and a temperature of 40-120°C;

[0054] By subjecting the formed membrane to alkalinization or acidification treatment, an ion exchange membrane having a permeable surface oriented structure can be obtained.

[0055] The polymer main chain in polymer A is one of polyimide, polyamide, polyetheretherketone, polysulfone, polyethersulfone, polytetrafluoroethylene, polydimethylsiloxane, polystyrene, polybenzimidazole, polyphenylene ether, polyethylene, polyvinyl chloride, polyvinylpyridine or polyvinylcyclohexane; the magnetic responsive structure of polymer A is one of ferrocenium cation group, cobaltocene cation group, nickelocene cation group and ferrocyanide coordination group.

[0056] Filler a is one of modified iron oxide particles, modified erbium oxide particles, modified carbon nanotubes, modified halloysite, modified rectorite, modified montmorillonite, modified silicon dioxide, modified titanium dioxide, modified graphene, modified graphene oxide, modified boron nitride or modified nitrogen carbide; the magnetic responsive structure of filler a is iron oxide, erbium oxide or a Prussian blue analogue.

[0057] The polymer B is one of polyimide, polysulfone, polyethersulfone, polystyrene, polyphenylene sulfide, polyvinylpyridine, polypropylene, polyacrylonitrile, polyphosphazene, polyvinylidene fluoride or polymethyl methacrylate.

[0058] When polymer A and polymer B are used to prepare the membrane-forming solution, the mass ratio is (1-99): (1-99); when polymer A and filler a are used to prepare the membrane-forming solution, the mass ratio is (50-99): (1-50); when polymer B and filler a are used to prepare the membrane-forming solution, the mass ratio is (50-99): (1-50); when polymer A, polymer B and filler a are used to prepare the membrane-forming solution, the mass ratio is (1-98): (1-98): (1-50).

[0059] The ion replacement agent is one of sodium molybdate, sodium tungstate, potassium tetrafluoroborate, potassium hexafluorophosphate, potassium hexafluoroantimonate, lithium bis(trifluoromethanesulfonyl imide), gadolinium nitrate, terbium chloride, dysprosium chloride, holmium nitrate, erbium nitrate, and thulium bromide.

[0060] The single solvent is one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide and m-cresol.

[0061] The mixed solvents with boiling point difference of no more than 4 degrees Celsius under normal pressure conditions are a group selected from N,N-dimethylformamide and 1-methylcyclohexanol, N,N-dimethylacetamide and 2-methylcyclohexanol, dimethyl sulfoxide and 3-nonanol, dimethyl sulfoxide and 1,2-butanediol, dimethyl sulfoxide and 2-ethylbutyric acid, N-methylpyrrolidone and 5-methyl-5-nonanol, N-methylpyrrolidone and α-phenylethanol, m-cresol and 5-methyl-5-nonanol, m-cresol and α-phenylethanol, and the volume ratio of the two solvent components in the mixed solvent is (10~90):(10~90).

[0062] The modification is surface quaternization, or a three-step combination of surface Prussian blue analog coating electrodeposition-catechol coating deposition-sulfonation.

[0063] The detailed embodiment of the method for preparing the ion exchange membrane having the permeable surface orientation structure is as follows:

[0064] Embodiment 1:

[0065] The polyimide and polystyrene having a ferrocenium cationic group structure in a mass ratio of 99:1 are subjected to ion replacement in a sodium molybdate aqueous solution, and after washing away excess ions, they are dissolved in a mixed solvent to prepare a membrane-forming solution, and after the membrane-forming solution is fully dissolved, it is allowed to stand for degassing; the membrane-forming solution is poured into a culture dish, and the solvent is evaporated at a temperature of 120° C. for 12 hours under the condition of a vertical magnetic field strength of 5 Tesla to form a membrane; the membrane is subjected to an alkalization treatment to obtain an ion exchange membrane with a permeable surface oriented structure;

[0066] Furthermore, the mixed solvent in Example 1 is: m-cresol and 5-methyl-5-nonanol in a volume ratio of 75:25, and the boiling point difference under normal pressure conditions is no more than 4 degrees Celsius.

[0067] Embodiment 2:

[0068] Polyamide with a cobaltocene cationic group structure, polyphenylene sulfide and surface quaternized erbium oxide particles with a mass ratio of 98:1:1 are subjected to ion replacement in a sodium tungstate aqueous solution, and after washing away excess ions, they are dissolved in N,N-dimethylacetamide to prepare a membrane-forming solution, which is allowed to stand for degassing after being fully dissolved; the membrane-forming solution is poured into a culture dish, and the solvent is evaporated at a temperature of 80°C for 30 hours under the condition of a vertical magnetic field intensity of 4 Tesla to form a film; the membrane is alkalized to obtain an ion exchange membrane with a permeable surface oriented structure.

[0069] Embodiment 3:

[0070] Polyetheretherketone with a nickelocene cationic group structure, polyvinylpyridine and surface quaternized erbium oxide particles with a mass ratio of 1:98:1 are subjected to ion replacement in a potassium tetrafluoroborate aqueous solution, and after washing away excess ions, they are dissolved in N-methylpyrrolidone to prepare a membrane-forming solution, which is allowed to stand for degassing after being fully dissolved; the membrane-forming solution is poured into a culture dish, and the solvent is evaporated at a temperature of 40°C for 48 hours under the condition of a vertical magnetic field intensity of 5 Tesla to form a film; the membrane is alkalized to obtain an ion exchange membrane with a permeable surface oriented structure.

[0071] Embodiment 4:

[0072] The polysulfone, polyimide and surface quaternized iron oxide particles with a ferrocene cationic group structure in a mass ratio of 40:40:20 are subjected to ion replacement in a potassium hexafluorophosphate aqueous solution, and the excess ions are washed away and then dissolved in a mixed solvent to prepare a membrane-forming solution, which is allowed to stand for degassing after being fully dissolved; the membrane-forming solution is poured into a culture dish, and the solvent is evaporated at a temperature of 90° C. for 24 hours under the condition of a vertical magnetic field strength of 3 Tesla to form a membrane; the membrane is subjected to an alkalization treatment to obtain an ion exchange membrane with a permeable surface oriented structure;

[0073] Furthermore, the mixed solvent in Example 4 is: m-cresol and α-phenylethanol in a volume ratio of 75:25, and the boiling point difference under normal pressure conditions is no more than 4 degrees Celsius.

[0074] Embodiment 5:

[0075] Polyethersulfone and polysulfone with a ferrocene cationic group structure in a mass ratio of 1:99 are subjected to ion replacement in a potassium hexafluoroantimonate aqueous solution, and after washing away excess ions, they are dissolved in meta-cresol to prepare a membrane-forming solution, which is allowed to stand for degassing after being fully dissolved; the membrane-forming solution is poured into a culture dish, and the solvent is evaporated at a temperature of 100°C for 24 hours under the condition of a vertical magnetic field intensity of 5 Tesla to form a film; the membrane is alkalized to obtain an ion exchange membrane with a permeable surface oriented structure.

[0076] Embodiment 6:

[0077] Polytetrafluoroethylene with a ferrocene cationic group structure and surface quaternized iron oxide particles with a mass ratio of 50:50 are subjected to ion replacement in an aqueous solution of lithium bis(trifluoromethanesulfonyl)imide, and after washing away excess ions, they are dissolved in N,N-dimethylformamide to prepare a membrane-forming solution, and after being fully dissolved, they are allowed to stand for degassing; the membrane-forming solution is poured into a culture dish, and the solvent is evaporated at a temperature of 70°C for 36 hours under the condition of a vertical magnetic field strength of 0.5 Tesla to form a film; the membrane is alkalized to obtain an ion exchange membrane with a permeable surface oriented structure.

[0078] Embodiment 7:

[0079] The polyetheretherketone having a ferrocenium cationic group structure and the erbium oxide particles modified by surface quaternization at a mass ratio of 99:1 are dissolved in a mixed solvent to prepare a membrane-forming solution, and after being fully dissolved, the solution is allowed to stand for degassing; the membrane-forming solution is poured into a culture dish, and the solvent is evaporated at a temperature of 110° C. for 18 hours under the condition of a vertical magnetic field strength of 3 Tesla to form a membrane; the membrane is subjected to an alkalization treatment to obtain an ion exchange membrane having a permeable surface oriented structure;

[0080] Furthermore, the mixed solvent in Example 7 is: N,N-dimethylformamide and 1-methylcyclohexanol in a volume ratio of 90:10, and the boiling point difference under normal pressure conditions is no more than 4 degrees Celsius.

[0081] Embodiment 8:

[0082] The polysulfone having a ferrocene cationic group structure is dissolved in a mixed solvent to prepare a membrane-forming solution, and after being fully dissolved, the membrane-forming solution is allowed to stand for degassing; the membrane-forming solution is poured into a culture dish, and the solvent is evaporated at a temperature of 85° C. for 24 hours under the condition of a vertical magnetic field strength of 1.5 Tesla to form a membrane; the membrane is subjected to an alkalization treatment to obtain an ion exchange membrane having a permeable surface oriented structure;

[0083] Furthermore, the mixed solvent in Example 8 is: N,N-dimethylformamide and 1-methylcyclohexanol in a volume ratio of 60:40, and the boiling point difference under normal pressure conditions is no more than 4 degrees Celsius.

[0084] Embodiment 9:

[0085] The polyethersulfone and the surface quaternized iron oxide particles with a mass ratio of 99:1 are subjected to ion replacement in a sodium tungstate aqueous solution, and the excess ions are washed away and then dissolved in a mixed solvent to prepare a membrane-forming solution, which is allowed to stand for degassing after being fully dissolved; the membrane-forming solution is poured into a culture dish, and the solvent is evaporated at a temperature of 60°C for 36 hours under the condition of a vertical magnetic field strength of 0.001 Tesla to form a membrane; the membrane is subjected to an alkalization treatment to obtain an ion exchange membrane with a permeable surface oriented structure;

[0086] Furthermore, the mixed solvent in Example 9 is: N,N-dimethylacetamide and 2-methylcyclohexanol in a volume ratio of 40:60, and the boiling point difference under normal pressure conditions is no more than 4 degrees Celsius.

[0087] Embodiment 10:

[0088] Polystyrene and polypropylene with a ferrocyanide coordination group structure and silicon dioxide modified by a three-step combination of surface Prussian blue analog coating electrodeposition-catechol coating deposition-sulfonation in a mass ratio of 25:25:50 are subjected to ion replacement in a gadolinium nitrate aqueous solution, and after washing away excess ions, they are dissolved in N,N-dimethylformamide to form a membrane-forming solution, which is allowed to stand for degassing after being fully dissolved; the membrane-forming solution is poured into a culture dish, and the solvent is evaporated at a temperature of 80°C for 30 hours under the condition of a vertical magnetic field strength of 0.1 Tesla to form a film; the membrane is acidified to obtain an ion exchange membrane with a permeable surface oriented structure.

[0089] Embodiment 11:

[0090] Polybenzimidazole with a ferrocyanide coordination group structure, polyacrylonitrile and titanium dioxide modified by a three-step combination of surface Prussian blue analog coating electrodeposition-catechol coating deposition-sulfonation in a mass ratio of 70:15:15 are subjected to ion replacement in a terbium chloride aqueous solution, and after washing away excess ions, the solution is dissolved in N,N-dimethylacetamide to form a membrane-forming solution, which is allowed to stand for degassing after being fully dissolved; the membrane-forming solution is poured into a culture dish, and the solvent is evaporated at a temperature of 110°C for 25 hours under the condition of a vertical magnetic field strength of 4 Tesla to form a film; the membrane is acidified to obtain an ion exchange membrane with a permeable surface oriented structure.

[0091] Embodiment 12:

[0092] Polyphenylene ether with a ferrocyanide coordination group structure, polyphosphazene and carbon nanotubes modified by a three-step combination of surface Prussian blue analog coating electrodeposition-catechol coating deposition-sulfonation in a mass ratio of 40:50:10 are subjected to ion replacement in a dysprosium chloride aqueous solution, and after washing away excess ions, the solution is dissolved in N-methylpyrrolidone to form a membrane-forming solution, which is allowed to stand for degassing after being fully dissolved; the membrane-forming solution is poured into a culture dish, and the solvent is evaporated at a temperature of 100°C for 30 hours under the condition of a vertical magnetic field intensity of 3 Tesla to form a film; the membrane is acidified to obtain an ion exchange membrane with a permeable surface oriented structure.

[0093] Embodiment 13:

[0094] Halloysite modified by three steps of polyvinylidene fluoride and surface Prussian blue analog coating electrodeposition-catechol coating deposition-sulfonation in a mass ratio of 50:50 is subjected to ion replacement in an aqueous solution of holmium nitrate, and after washing away excess ions, it is dissolved in dimethyl sulfoxide to prepare a membrane-forming solution, which is allowed to stand for degassing after being fully dissolved; the membrane-forming solution is poured into a culture dish, and the solvent is evaporated at a temperature of 90°C for 35 hours under the condition of a vertical magnetic field intensity of 4 Tesla to form a film; the membrane is acidified to obtain an ion exchange membrane with a permeable surface oriented structure.

[0095] Embodiment 14:

[0096] Rectorite modified by three-step combination of polyvinyl chloride with ferrocyanide coordination group structure, polymethyl methacrylate and surface Prussian blue analog coating electrodeposition-catechol coating deposition-sulfonation in a mass ratio of 60:20:20 is subjected to ion replacement in an erbium nitrate aqueous solution, and after washing away excess ions, it is dissolved in m-cresol to prepare a membrane-forming solution, which is allowed to stand for degassing after being fully dissolved; the membrane-forming solution is poured into a culture dish, and the solvent is evaporated at a temperature of 90°C for 30 hours under the condition of a vertical magnetic field intensity of 5 Tesla to form a film; the membrane is acidified to obtain an ion exchange membrane with a permeable surface oriented structure.

[0097] Embodiment 15:

[0098] The polyvinyl cyclohexane with a ferrocyanide coordination group structure and the graphene modified by the three-step combination of surface Prussian blue analog coating electrodeposition-catechol coating deposition-sulfonation in a mass ratio of 70:30 are dissolved in a mixed solvent to prepare a membrane-making solution, and after being fully dissolved, the solution is allowed to stand for degassing; the membrane-making solution is poured into a culture dish, and the solvent is evaporated at a temperature of 40° C. for 48 hours under the condition of a vertical magnetic field strength of 5 Tesla to form a membrane; the membrane is acidified to obtain an ion exchange membrane with a permeable surface orientation structure;

[0099] Furthermore, the mixed solvent in Example 15 is: dimethyl sulfoxide and 3-nonanol in a volume ratio of 65:35, and the boiling point difference under normal pressure conditions is no more than 4 degrees Celsius.

[0100] Embodiment 16:

[0101] The polyvinyl pyridine having a ferrocyanide coordination group structure is dissolved in a mixed solvent to prepare a membrane-forming solution, and after being fully dissolved, it is allowed to stand for degassing; the membrane-forming solution is poured into a culture dish, and the solvent is evaporated at a temperature of 110° C. for 25 hours under the condition of a vertical magnetic field strength of 4 Tesla to form a membrane; the membrane is acidified to obtain an ion exchange membrane having a permeable surface oriented structure;

[0102] Furthermore, the mixed solvent in Example 16 is: dimethyl sulfoxide and 1,2-butanediol in a volume ratio of 10:90, and the boiling point difference under normal pressure conditions is no more than 4 degrees Celsius.

[0103] Embodiment 17:

[0104] The polyphenylene ether with a ferrocyanide coordination group structure and the graphene oxide modified by the three-step combination of surface Prussian blue analog coating electrodeposition-catechol coating deposition-sulfonation in a mass ratio of 85:15 are dissolved in a mixed solvent to prepare a membrane-making solution, and after being fully dissolved, the solution is allowed to stand for degassing; the membrane-making solution is poured into a culture dish, and the solvent is evaporated at a temperature of 100° C. for 40 hours under the condition of a vertical magnetic field strength of 3 Tesla to form a membrane; the membrane is acidified to obtain an ion exchange membrane with a permeable surface orientation structure;

[0105] Furthermore, the mixed solvent in Example 17 is: dimethyl sulfoxide and 2-ethylbutyric acid in a volume ratio of 80:20, and the boiling point difference under normal pressure conditions is no more than 4 degrees Celsius.

[0106] Embodiment 18:

[0107] The polyethylene with a ferrocyanide coordination group structure and the boron nitride modified by the three-step combination of surface Prussian blue analog coating electrodeposition-catechol coating deposition-sulfonation in a mass ratio of 60:40 are dissolved in a mixed solvent to prepare a membrane-making solution, and after being fully dissolved, the membrane-making solution is allowed to stand for degassing; the membrane-making solution is poured into a culture dish, and the solvent is evaporated at a temperature of 90° C. for 35 hours under the condition of a vertical magnetic field strength of 4 Tesla to form a membrane; the membrane is acidified to obtain an ion exchange membrane with a permeable surface oriented structure;

[0108] Furthermore, the mixed solvent in Example 18 is: N-methylpyrrolidone and α-phenylethanol in a volume ratio of 50:50, and the boiling point difference under normal pressure conditions is no more than 4 degrees Celsius.

[0109] Embodiment 19:

[0110] The polyvinyl cyclohexane with a ferrocyanide coordination group structure and the carbonized nitrogen modified by the three-step combination of surface Prussian blue analog coating electrodeposition-catechol coating deposition-sulfonation in a mass ratio of 99:1 are dissolved in a mixed solvent to prepare a membrane-making solution, and after being fully dissolved, the solution is allowed to stand for degassing; the membrane-making solution is poured into a culture dish, and the solvent is evaporated at a temperature of 90° C. for 30 hours under the condition of a vertical magnetic field strength of 5 Tesla to form a membrane; the membrane is acidified to obtain an ion exchange membrane with a permeable surface oriented structure;

[0111] Furthermore, the mixed solvent in Example 19 is: N-methylpyrrolidone and α-phenylethanol in a volume ratio of 30:70, and the boiling point difference under normal pressure conditions is no more than 4 degrees Celsius.

[0112] Embodiment 20:

[0113] The polyethylene with a ferrocyanide coordination group structure and the montmorillonite modified by the three-step combination of surface Prussian blue analog coating electrodeposition-catechol coating deposition-sulfonation in a mass ratio of 65:35 are subjected to ion replacement in a thulium bromide aqueous solution, and the excess ions are washed away and dissolved in a mixed solvent to prepare a membrane-forming solution, which is allowed to stand for degassing after being fully dissolved; the membrane-forming solution is poured into a culture dish, and the solvent is evaporated at a temperature of 60°C for 45 hours under the condition of a vertical magnetic field strength of 4.5 Tesla to form a film; the membrane is acidified to obtain an ion exchange membrane with a permeable surface orientation structure;

[0114] Furthermore, the mixed solvent in Example 20 is: N-methylpyrrolidone and 5-methyl-5-nonanol in a volume ratio of 60:40, and the boiling point difference under normal pressure conditions is no more than 4 degrees Celsius.

[0115] Comparative Example 1-1:

[0116] The only difference between Comparative Example 1-1 and Example 1 is that Comparative Example 1-1 does not perform ion replacement of the raw materials before membrane formation, but directly dissolves m-cresol and 5-methyl-5-nonanol in a volume ratio of 75:25 to prepare the membrane liquid, and the rest is consistent with Example 1.

[0117] Comparative Example 1-2:

[0118] The only difference between Comparative Example 1-2 and Comparative Example 1-1 is that, in Comparative Example 1-2, the raw materials are dissolved in m-cresol and 1-methylcyclohexanol in a volume ratio of 75:25 to prepare the membrane-making liquid, and the boiling point difference under normal pressure conditions is greater than 4 degrees Celsius, and the rest is consistent with Comparative Example 1-1.

[0119] Comparative Examples 1-3:

[0120] The only difference between Comparative Example 1-3 and Comparative Example 1-2 is that, in Comparative Example 1-3, the raw materials are dissolved in a single meta-acetic acid to prepare the film-making liquid, and the rest is the same as Comparative Example 1-2.

[0121] Comparative Example 2:

[0122] The difference between Comparative Example 2 and Example 2 is that Comparative Example 2 does not carry out ion replacement of raw materials before membrane formation, and the rest is consistent with Example 2.

[0123] Comparative Example 3:

[0124] The difference between Comparative Example 3 and Example 3 is that Comparative Example 3 does not carry out ion replacement of raw materials before membrane formation, and the rest is consistent with Example 3.

[0125] Comparative Example 4-1:

[0126] The only difference between Comparative Example 4-1 and Example 4 is that, in Comparative Example 4-1, the raw materials are not subjected to ion replacement before film formation, but are directly dissolved in m-cresol and α-phenylethanol in a volume ratio of 75:25 to prepare the film-forming solution, and the rest are consistent with Example 4.

[0127] Comparative Example 4-2:

[0128] The difference between Comparative Example 4-2 and Comparative Example 4-1 is that in Comparative Example 4-2, the raw materials are dissolved in m-cresol and 2-methylcyclohexanol in a volume ratio of 75:25 to prepare the membrane-making liquid, and the boiling point difference under normal pressure conditions is greater than 4 degrees Celsius, and the rest is consistent with Comparative Example 4-1.

[0129] Comparative Example 4-3:

[0130] The only difference between Comparative Example 4-3 and Comparative Example 4-2 is that in Comparative Example 4-3, the raw materials are dissolved in a single m-cresol to prepare the membrane-making solution, and the rest is consistent with Example 4-2.

[0131] Comparative Example 5:

[0132] The difference between Comparative Example 5 and Example 5 is that Comparative Example 5 does not carry out ion replacement of raw materials before membrane formation, and the rest is consistent with Example 5.

[0133] Comparative Example 6:

[0134] The only difference between Comparative Example 6 and Example 6 is that Comparative Example 6 does not carry out ion replacement of raw materials before membrane formation, and the rest is consistent with Example 6.

[0135] Comparative Example 7-1:

[0136] The only difference between Comparative Example 7-1 and Example 7 is that, in Comparative Example 7-1, the raw materials are dissolved in N,N-dimethylformamide and 5-methyl-5-nonanol in a volume ratio of 90:10 to prepare the membrane liquid, and the boiling point difference between N,N-dimethylformamide and 5-methyl-5-nonanol under normal pressure conditions is greater than 4 degrees Celsius, and the rest is consistent with Example 7.

[0137] Comparative Example 7-2:

[0138] The only difference between Comparative Example 7-2 and Example 7-1 is that in Comparative Example 7-2, the raw materials are dissolved in a single N,N-dimethylformamide to prepare the membrane-forming solution, and the rest is consistent with Example 7-1.

[0139] Comparative Example 8-1:

[0140] The only difference between Comparative Example 8-1 and Example 8 is that in Comparative Example 8-1, the raw materials are dissolved in N,N-dimethylformamide and α-phenylethanol in a volume ratio of 60:40 to prepare a membrane-making solution, and the boiling point difference between N,N-dimethylformamide and α-phenylethanol under normal pressure conditions is greater than 4 degrees Celsius. The rest is consistent with Example 8.

[0141] Comparative Example 8-2:

[0142] The only difference between Comparative Example 8-2 and Example 8-1 is that in Comparative Example 8-2, the raw materials are dissolved in a single N,N-dimethylformamide to prepare the membrane-forming solution, and the rest is consistent with Example 8-1.

[0143] Comparative Example 9-1:

[0144] The only difference between Comparative Example 9-1 and Example 9 is that Comparative Example 9-1 does not perform ion replacement of the raw materials before membrane formation, but directly dissolves in N,N-dimethylacetamide and 2-methylcyclohexanol in a volume ratio of 40:60. The rest is consistent with Example 9.

[0145] Comparative Example 9-2:

[0146] The only difference between Example 9-2 and Example 9-1 is that in Example 9-2, the raw materials are dissolved in N,N-dimethylacetamide and 3-nonanol in a volume ratio of 40:60 to prepare the membrane-making liquid, and the boiling point difference under normal pressure conditions is greater than 4 degrees Celsius. The rest is consistent with Example 9-1.

[0147] Comparative Example 9-3:

[0148] The only difference between Comparative Example 9-3 and Comparative Example 9-2 is that in Comparative Example 9-3, the raw materials are dissolved in a single N,N-dimethylacetamide to prepare the membrane-making solution, and the rest is consistent with Comparative Example 9-2.

[0149] Comparative Example 10:

[0150] The difference between Comparative Example 10 and Example 10 is that Comparative Example 10 does not carry out ion replacement of raw materials before membrane formation, and the rest is consistent with Example 10.

[0151] Comparative Example 11:

[0152] The only difference between Comparative Example 11 and Example 11 is that Comparative Example 11 does not carry out ion replacement of raw materials before membrane formation, and the rest is consistent with Example 11.

[0153] Comparative Example 12:

[0154] The only difference between Comparative Example 12 and Example 12 is that Comparative Example 12 does not carry out ion replacement of the raw materials before membrane formation, and the rest is consistent with Example 12.

[0155] Comparative Example 13:

[0156] The only difference between Comparative Example 13 and Example 13 is that Comparative Example 13 does not carry out ion replacement of raw materials before membrane formation, and the rest is consistent with Example 13.

[0157] Comparative Example 14:

[0158] The only difference between Comparative Example 14 and Example 14 is that Comparative Example 14 does not carry out ion replacement of the raw materials before membrane formation, and the rest is consistent with Example 14.

[0159] Comparative Example 15-1:

[0160] The only difference between Comparative Example 15-1 and Example 15 is that, in Comparative Example 15-1, the raw materials are dissolved in dimethyl sulfoxide and 1-methylcyclohexanol in a volume ratio of 65:35 to prepare the membrane-making solution, and the boiling point difference between dimethyl sulfoxide and 1-methylcyclohexanol under normal pressure conditions is greater than 4 degrees Celsius. The rest is consistent with Example 15.

[0161] Comparative Example 15-2:

[0162] The only difference between Comparative Example 15-2 and Example 15 is that in Comparative Example 15-2, the raw materials are dissolved in a single dimethyl sulfoxide to prepare the membrane-forming solution, and the rest is consistent with Example 15.

[0163] Comparative Example 16-1:

[0164] The only difference between Comparative Example 16-1 and Example 16 is that, in Comparative Example 16-1, the raw materials are dissolved in dimethyl sulfoxide and 2-methylcyclohexanol in a volume ratio of 10:90 to prepare the membrane-making solution, and the boiling point difference between dimethyl sulfoxide and 2-methylcyclohexanol under normal pressure conditions is greater than 4 degrees Celsius. The rest is consistent with Example 16.

[0165] Comparative Example 16-2:

[0166] The only difference between Comparative Example 16-2 and Example 16 is that in Comparative Example 16-2, the raw materials are dissolved in a single dimethyl sulfoxide to prepare the membrane-forming solution, and the rest is consistent with Example 16.

[0167] Comparative Example 17-1:

[0168] The only difference between Comparative Example 17-1 and Example 17 is that, in Comparative Example 17-1, the raw materials are dissolved in dimethyl sulfoxide and 1-methylcyclohexanol in a volume ratio of 80:20 to prepare the membrane liquid, and the boiling point difference between dimethyl sulfoxide and 1-methylcyclohexanol under normal pressure conditions is greater than 4 degrees Celsius. The rest is consistent with Example 17.

[0169] Comparative Example 17-2:

[0170] The only difference between Comparative Example 17-2 and Example 17 is that in Comparative Example 17-2, the raw materials are dissolved in a single dimethyl sulfoxide to prepare the membrane-forming solution, and the rest is consistent with Example 17.

[0171] Comparative Example 18-1:

[0172] The only difference between Comparative Example 18-1 and Example 18 is that in Comparative Example 18-1, the raw materials are dissolved in N-methylpyrrolidone and 1,2-butanediol in a volume ratio of 50:50 to prepare the membrane-making liquid, and the boiling point difference between N-methylpyrrolidone and 1,2-butanediol under normal pressure conditions is greater than 4 degrees Celsius. The rest is consistent with Example 18.

[0173] Comparative Example 18-2:

[0174] The only difference between Comparative Example 18-2 and Example 18 is that in Comparative Example 18-2, the raw materials are dissolved in a single N-methylpyrrolidone to prepare the membrane-forming solution, and the rest is consistent with Example 18.

[0175] Comparative Example 19-1:

[0176] The only difference between Comparative Example 19-1 and Example 19 is that in Comparative Example 19-1, the raw materials are dissolved in N-methylpyrrolidone and 2-ethylbutyric acid in a volume ratio of 30:70 to prepare the membrane-making liquid, and the boiling point difference between N-methylpyrrolidone and 2-ethylbutyric acid under normal pressure conditions is greater than 4 degrees Celsius. The rest is consistent with Example 19.

[0177] Comparative Example 19-2:

[0178] The only difference between Comparative Example 19-2 and Example 19 is that in Comparative Example 19-2, the raw materials are dissolved in a single N-methylpyrrolidone to prepare the membrane-forming solution, and the rest is consistent with Example 19.

[0179] Comparative Example 20-1:

[0180] The only difference between Comparative Example 20-1 and Example 20 is that Comparative Example 20-1 does not carry out ion replacement of the raw materials before membrane formation, but directly dissolves them in N-methylpyrrolidone and 5-methyl-5-nonanol in a volume ratio of 60:40 to prepare the membrane liquid. The rest is consistent with Example 20.

[0181] Comparative Example 20-2:

[0182] The only difference between Comparative Example 20-2 and Comparative Example 20-1 is that in Comparative Example 20-2, the raw materials are dissolved in N-methylpyrrolidone and 2-methylcyclohexanol in a volume ratio of 60:40 to prepare the membrane-making liquid, and the boiling point difference under normal pressure conditions is greater than 4 degrees Celsius. The rest is consistent with Comparative Example 20-1.

[0183] Comparative Example 20-3:

[0184] The only difference between Comparative Example 20-3 and Comparative Example 20-2 is that in Comparative Example 20-3, the raw materials are dissolved in a single N-methylpyrrolidone to prepare the membrane-making solution, and the rest is consistent with Comparative Example 20-2.

[0185] The present invention conducts conductivity tests on the ion exchange membranes prepared in Examples 1-20 and the comparative examples, and the test results are shown in Table 1.1:

[0186] Table 1.1

[0187]

[0188] According to Table 1.1:

[0189] The degree of orientation of Example 1 is about 2.7 times that of Comparative Example 1-1;

[0190] This indicates that ion replacement of the raw materials before dissolving them in the mixed solvent can improve the conductivity and orientation degree in the permeable surface direction of the ion exchange membrane.

[0191] The orientation degree of comparative example 1-1 is about 2.3 times that of comparative example 1-2;

[0192] This indicates that when the boiling point difference of the mixed solvent is no more than 4 degrees Celsius, the conductivity and orientation degree of the ion exchange membrane in the permeable surface direction can be improved.

[0193] The orientation degree of Comparative Example 1-2 is almost the same as that of Comparative Example 1-3, but the conductivity in both the through-plane direction and the in-plane direction is improved;

[0194] This shows that the use of mixed solvents to prepare the membrane solution can improve the overall conductivity of the ion exchange membrane.

[0195] The orientation degree of Example 2 is increased to about 5.1 times that of Comparative Example 2; the orientation degree of Example 3 is increased to about 3.1 times that of Comparative Example 3; the orientation degree of Example 5 is increased to about 3.3 times that of Comparative Example 5; the orientation degree of Example 6 is increased to about 3.2 times that of Comparative Example 6; the orientation degree of Example 10 is increased to about 2.7 times that of Comparative Example 10; the orientation degree of Example 11 is increased to about 3.5 times that of Comparative Example 11; the orientation degree of Example 12 is increased to about 2.6 times that of Comparative Example 12; the orientation degree of Example 13 is increased to about 2.5 times that of Comparative Example 13; the orientation degree of Example 14 is increased to about 2.3 times that of Comparative Example 14;

[0196] This indicates that ion replacement before preparing the membrane-forming solution can improve the conductivity and orientation degree in the permeate direction of the ion exchange membrane.

[0197] The degree of orientation of Example 4 is about 2.9 times that of Comparative Example 4-1;

[0198] This indicates that ion replacement of the raw materials before dissolving them in the mixed solvent can improve the conductivity and orientation degree in the permeable surface direction of the ion exchange membrane.

[0199] The orientation degree of comparative example 4-1 is about 2.3 times that of comparative example 4-2;

[0200] This indicates that when the boiling point difference of the mixed solvent is no more than 4 degrees Celsius, the conductivity and orientation degree of the ion exchange membrane in the permeable surface direction can be improved.

[0201] The orientation degree of Comparative Example 4-2 is almost the same as that of Comparative Example 4-3, but the conductivity in both the through-plane direction and the in-plane direction is improved;

[0202] This shows that the use of mixed solvents to prepare the membrane solution can improve the overall conductivity of the ion exchange membrane.

[0203] The orientation degree of Example 7 is about 3.4 times that of Comparative Example 7-1; the orientation degree of Example 8 is about 2.7 times that of Comparative Example 8-1;

[0204] This indicates that when the boiling point difference of the mixed solvent is no more than 4 degrees Celsius, the conductivity and orientation degree of the ion exchange membrane in the permeable surface direction can be improved.

[0205] The orientation degree of Comparative Example 7-1 is almost the same as that of Comparative Example 7-2, but the conductivity in both the through-plane direction and the in-plane direction is improved; the orientation degree of Comparative Example 8-1 is almost the same as that of Comparative Example 8-2, but the conductivity in both the through-plane direction and the in-plane direction is improved;

[0206] This shows that the use of mixed solvents to prepare the membrane solution can improve the overall conductivity of the ion exchange membrane.

[0207] The degree of orientation of Example 9 is about 4.0 times that of Comparative Example 9-1;

[0208] This indicates that ion replacement of the raw materials before dissolving them in the mixed solvent can improve the conductivity and orientation degree in the permeable surface direction of the ion exchange membrane.

[0209] The orientation degree of Comparative Example 9-1 is about 2.2 times that of Comparative Example 9-2;

[0210] This indicates that when the boiling point difference of the mixed solvent is no more than 4 degrees Celsius, the conductivity and orientation degree of the ion exchange membrane in the permeable surface direction can be improved.

[0211] The orientation degree of Comparative Example 9-2 is almost the same as that of Comparative Example 9-3, but the conductivity in both the through-plane direction and the in-plane direction is improved;

[0212] This shows that the use of mixed solvents to prepare the membrane solution can improve the overall conductivity of the ion exchange membrane.

[0213] The orientation degree of Example 15 is about 4.6 times that of Comparative Example 15-1; the orientation degree of Example 16 is about 3.9 times that of Comparative Example 16-1; the orientation degree of Example 17 is about 3.0 times that of Comparative Example 17-2; the orientation degree of Example 18 is about 2.9 times that of Comparative Example 18-2; the orientation degree of Example 19 is about 2.9 times that of Comparative Example 19-2;

[0214] This indicates that when the boiling point difference of the mixed solvent is no more than 4 degrees Celsius, the conductivity and orientation degree of the ion exchange membrane in the permeable surface direction can be improved.

[0215] The orientation degree of Comparative Example 15-1 is almost the same as that of Comparative Example 15-2, but the conductivity in both the through-plane direction and the in-plane direction is improved; the orientation degree of Comparative Example 16-1 is almost the same as that of Comparative Example 16-2, but the conductivity in both the through-plane direction and the in-plane direction is improved; the orientation degree of Comparative Example 17-1 is almost the same as that of Comparative Example 17-2, but the conductivity in both the through-plane direction and the in-plane direction is improved; the orientation degree of Comparative Example 18-1 is almost the same as that of Comparative Example 18-2, but the conductivity in both the through-plane direction and the in-plane direction is improved; the orientation degree of Comparative Example 19-1 is almost the same as that of Comparative Example 19-2, but the conductivity in both the through-plane direction and the in-plane direction is improved;

[0216] This shows that the use of mixed solvents to prepare the membrane solution can improve the overall conductivity of the ion exchange membrane.

[0217] The degree of orientation of Example 20 is about 2.8 times that of Comparative Example 20-1;

[0218] This indicates that ion replacement of the raw materials before dissolving them in the mixed solvent can improve the conductivity and orientation degree in the permeable surface direction of the ion exchange membrane.

[0219] The orientation degree of comparative example 20-1 is about 1.6 times that of comparative example 20-2;

[0220] This indicates that when the boiling point difference of the mixed solvent is no more than 4 degrees Celsius, the conductivity and orientation degree of the ion exchange membrane in the permeable surface direction can be improved.

[0221] The orientation degree of comparative example 20-2 is almost the same as that of comparative example 20-3, but the conductivity in both the through-plane direction and the in-plane direction is improved;

[0222] This shows that the use of mixed solvents to prepare the membrane solution can improve the overall conductivity of the ion exchange membrane.

[0223] In order to further explain the reasons for the above performance differences, including the influence of ion replacement before membrane formation, and the influence of using a mixed solvent with a boiling point difference of no more than 4 degrees Celsius under normal pressure conditions (including two aspects: (1) the influence of using a single solvent to using a mixed solvent; (2) the influence of using a mixed solvent with a boiling point difference of more than 4 degrees Celsius under normal pressure conditions to using a mixed solvent with a boiling point difference of no more than 4 degrees Celsius under normal pressure conditions), the membrane liquid and the prepared ion exchange membrane were further characterized. In the present invention, in each embodiment and each comparative example using the same membrane raw material and the same magnetic field strength, the performance data of the membrane liquid and the prepared membrane structure are shown in Table 1.2:

[0224] Among them, the magnetization intensity of the membrane liquid was tested using a vibrating sample magnetometer at 1 Tesla and 25°C; the aggregation size and orientation regularity of the hydrophilic phase of the membrane were tested using small-angle X-ray scattering at 50% relative humidity and 25°C. The aggregation size of the hydrophilic phase of the membrane was calculated from the peak position of the small-angle X-ray scattering, and the ratio of the small-angle X-ray scattering peak height to the half-peak width characterized the orientation regularity of the hydrophilic phase of the membrane.

[0225] Table 1.2

[0226]

[0227] According to Table 1.2, in the examples and comparative examples using the same film-forming raw materials and magnetic field strength, ion replacement before film formation can significantly increase the magnetization intensity of the film-forming solution.

[0228] A mixed solvent with a boiling point difference of no more than 4 degrees Celsius under normal pressure conditions can significantly increase the aggregation size of the hydrophilic phase of the membrane and the regularity of the hydrophilic phase orientation.

[0229] The effect of ion replacement before film making in the present invention is:

[0230] Compared with the ions originally carried by the polymer or filler, the replaced ions can enhance the magnetization of the membrane solution and significantly improve the magnetic response, thereby preparing an ion exchange membrane with a higher degree of permeable surface orientation using the same membrane raw materials and the same magnetic field strength. If the ion replacement agent is not used for ion replacement before membrane formation, the magnetization of the membrane solution is low, and the orientation degree of the ion exchange membrane prepared with the same membrane raw materials and the same magnetic field strength is low, and the advantage of ion conductivity concentrated in the permeable surface direction is not obvious.

[0231] The use of mixed solvents with boiling points that differ by no more than 4 degrees Celsius under normal pressure has two effects:

[0232] On the one hand, compared with a single solvent, the two solvent components of a mixed solvent have certain polarity differences. One solvent component is more affinity with the hydrophilic phase with ion transmission ability in the membrane-making raw material, and the other solvent component is more affinity with the hydrophobic phase without ion transmission ability in the membrane-making raw material. Therefore, the mixed solvent can promote the separation of the hydrophilic and hydrophobic phases of the raw materials in the membrane-making liquid, making the aggregation size of the hydrophilic phase with ion transmission ability larger, and the size of the surface-oriented transmission channel formed under magnetic field conditions is also larger, which is more conducive to smooth ion transmission.

[0233] On the other hand, the condition that the boiling point difference is no more than 4 degrees Celsius under normal pressure conditions makes the mixed solvent have a similar volatilization rate during the volatilization process, ensuring that the two solvent components are volatilized completely at the same time. If a mixed solvent with a large difference in boiling point is used, after the mixed solvent helps to produce hydrophilic and hydrophobic phase separation, one solvent component will evaporate first during the film making process, leaving a higher content of the other solvent component, which will become a single solvent at this time, which will destroy the hydrophilic and hydrophobic phase separation produced by the mixed solvent in the early stage of film making, resulting in the difficulty of maintaining the large-sized through-surface oriented transmission channel until the final film is formed, resulting in size shrinkage and reduced regularity. Therefore, the boiling point difference of no more than 4 degrees Celsius under normal pressure conditions can better maintain the large size and regularity of the hydrophilic and hydrophobic phase separation produced by the mixed solvent during the entire film making process and the obtained oriented transmission channel.

[0234] These two effects can improve the ion transport performance advantage of the finally prepared ion exchange membrane in the permeation direction.

[0235] In summary, compared with the general film-making method, the present invention adopts the treatment technology of ion replacement before film-making, mixed solvents with boiling point difference of no more than 4 degrees Celsius under normal pressure conditions to prepare film-making liquid, or a combination of the two. Under the condition of the same film-making raw materials and the same magnetic field strength, the magnetic response ability of the film-making liquid can be enhanced, and the aggregation size and orientation regularity of the hydrophilic phase in the whole film-making process can be improved. This method breaks through the limitations of only synthesizing polymers or fillers with electric field or magnetic field responsiveness and film-making under electric field or magnetic field conditions, and comprehensively considers and optimizes important factors such as ions and solvents in the whole film-making system and process, greatly improving the orientation degree of ion exchange membranes, and obtaining more significant ion transmission performance benefits in the direction of the permeation surface.

[0236] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing an ion exchange membrane having a permeable surface oriented structure, characterized in that: The method comprises the following steps: S001: using a polymer A having a magnetic responsive structure alone or using one of the following compositions, performing ion replacement on an ion replacement agent aqueous solution before film formation, washing away excess ions and dissolving in a single solvent to prepare a film-forming solution; the composition comprises composition ① and / or composition ②, wherein: composition ① is a combination of any two of polymer B, polymer A having a magnetic responsive structure and filler a having a magnetic responsive structure; composition ② is a combination of polymer B, polymer A having a magnetic responsive structure and filler a having a magnetic responsive structure; S002: pouring the film-forming solution into a culture dish, and under the conditions of a vertical magnetic field strength of 0.001-5 Tesla and a temperature of 40-120° C., evaporating the solvent for 12-48 hours to achieve film formation; S003: alkalizing or acidifying the formed film to obtain an ion exchange membrane having a permeable surface oriented structure.

2. The method for preparing an ion exchange membrane having a permeable surface oriented structure according to claim 1, characterized in that: In step S001, the film-forming liquid can also be prepared by the following steps: using polymer A with a magnetic responsive structure alone or using one of the following compositions, performing ion replacement in an ion replacement agent aqueous solution before film formation, washing away excess ions and dissolving in a mixed solvent with a boiling point difference of no more than 4 degrees Celsius under normal pressure to prepare a film-forming liquid; the composition includes: ①: a combination of any two of polymer B, polymer A with a magnetic responsive structure and filler a with a magnetic responsive structure; ②: a combination of polymer B, polymer A with a magnetic responsive structure and filler a with a magnetic responsive structure.

3. The method for preparing an ion exchange membrane having a permeable surface oriented structure according to claim 1, characterized in that: The polymer main chain in the polymer A is one of polyimide, polyamide, polyetheretherketone, polysulfone, polyethersulfone, polytetrafluoroethylene, polydimethylsiloxane, polystyrene, polybenzimidazole, polyphenylene ether, polyethylene, polyvinyl chloride, polyvinylpyridine or polyvinylcyclohexane; the magnetic responsive structure of the polymer A is one of ferrocenium cation group, cobaltocene cation group, nickelocene cation group and ferrocyanide coordination group.

4. The method for preparing an ion exchange membrane having a permeable surface oriented structure according to claim 1, characterized in that: The filler a is one of modified iron oxide particles, modified erbium oxide particles, modified carbon nanotubes, modified halloysite, modified rectorite, modified montmorillonite, modified silicon dioxide, modified titanium dioxide, modified graphene, modified graphene oxide, modified boron nitride or modified nitrogen carbide; the magnetic responsive structure of the filler a is iron oxide, erbium oxide or a Prussian blue analogue.

5. The method for preparing an ion exchange membrane having a permeable surface oriented structure according to claim 1, characterized in that: The polymer B is one of polyimide, polysulfone, polyethersulfone, polystyrene, polyphenylene sulfide, polyvinylpyridine, polypropylene, polyacrylonitrile, polyphosphazene, polyvinylidene fluoride or polymethyl methacrylate.

6. The method for preparing an ion exchange membrane having a permeable surface oriented structure according to claim 1, characterized in that: When the polymer A and polymer B are used to prepare the membrane-making solution, the mass ratio is (1-99): (1-99); when the polymer A and filler a are used to prepare the membrane-making solution, the mass ratio is (50-99): (1-50); when the polymer B and filler a are used to prepare the membrane-making solution, the mass ratio is (50-99): (1-50); when the polymer A, polymer B and filler a are used to prepare the membrane-making solution, the mass ratio is (1-98): (1-98): (1-50).

7. The method for preparing an ion exchange membrane having a permeable surface oriented structure according to claim 1, characterized in that: The ion replacement agent is one of sodium molybdate, sodium tungstate, potassium tetrafluoroborate, potassium hexafluorophosphate, potassium hexafluoroantimonate, lithium bis(trifluoromethanesulfonyl imide), gadolinium nitrate, terbium chloride, dysprosium chloride, holmium nitrate, erbium nitrate, and thulium bromide; the single solvent is one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, and m-cresol.

8. The method for preparing an ion exchange membrane having a permeable surface oriented structure according to claim 2, characterized in that: The mixed solvent with a boiling point difference of no more than 4 degrees Celsius under normal pressure conditions is a group selected from N,N-dimethylformamide and 1-methylcyclohexanol, N,N-dimethylacetamide and 2-methylcyclohexanol, dimethyl sulfoxide and 3-nonanol, dimethyl sulfoxide and 1,2-butanediol, dimethyl sulfoxide and 2-ethylbutyric acid, N-methylpyrrolidone and 5-methyl-5-nonanol, N-methylpyrrolidone and α-phenylethanol, m-cresol and 5-methyl-5-nonanol, m-cresol and α-phenylethanol, and the volume ratio of the two solvent components in the mixed solvent is (10-90): (10-90).

9. The method for preparing an ion exchange membrane having a permeable surface oriented structure according to claim 4, characterized in that: The modification is surface quaternization, or a three-step combination of surface Prussian blue analog coating electrodeposition-catechol coating deposition-sulfonation.

Citation Information

Patent Citations

  • A multi-layer film material for switching bias magnetic and electric resistance sensor part

    CN101150171A

  • Preparation method of ion exchange membrane with ordered ionic conduction structure

    CN109078501A

  • Preparation method of anion exchange membranes with microporous polymer

    CN111019182A

  • Guanidyl functionalized anion exchange membrane with cross-linked network structure and preparation method thereof

    CN111393696A

  • Ion-exchange membrane with preferentially oriented morphological texture

    US20160276688A1